Cobalt (II) phthalocyanine derived Co3O4@HCNFs as highly effective bifunctional electrocatalysts for iodide redox couple reduction (IRR) and oxygen reduction reaction (ORR) - Ziyu Guo; Wenyu Gong; Jianing Guo; Mingxing Wu (Next Materials)
Developing low-cost electrocatalysts for iodide redox couple reduction (IRR) and oxygen reduction reaction (ORR), applied in dye-sensitized solar cells (DSCs) and Zinc-air batteries (ZABs) is of crucial significance for the fields of energy conversion and energy storage. Herein, nitrogen-enriched hollow carbon nanofibers with opens at both ends (HCNFs) are first synthesized, which show decent catalytic activity for the IRR, and a power conversion efficiency (PCE) of 6.95 % is achieved by the corresponding DSCs. Cobalt (II) phthalocyanine derived Co3O4 incorporated HCNFs (Co3O4@HCNFs) are further prepared to improve the catalytic activity, generating a high PCE of 8.36 %, indicating a photovoltaic enhancement of 20.3 % as compared with HCNFs. Similarly, Co3O4@HCNFs also exhibit excellent ORR performance, and the half-wave potential (E1/2) is up to 0.827 V, with the limiting current density (Jlim) improved to 4.54 mA·cm−2. In contrast, the E1/2 and Jlim of the pristine HCNFs are 0.630 V and 3.99 mA·cm−2, respectively, much lower than those of Co3O4@HCNFs. The remarkable catalytic activity of Co3O4@HCNFs can be ascribed the introduced Co3O4, resulting in additional active sites of Co-N-C, and the synergistic effects between metals and carbon also accounts for the enhanced catalytic activity. Moreover, the specific hollow structure with opens at both ends is beneficial for mass diffusion to ensure sufficient contact between the electrolyte and the electrocatalysts, which is also a possible reason for the high catalytic activity of Co3O4@HCNFs. This work is expected to provide a feasible strategy for exploring low-cost and highly effective bifunctional IRR/ORR electrocatalysts for DSCs and ZABs.